2020
DOI: 10.3758/s13414-020-02122-y
|View full text |Cite
|
Sign up to set email alerts
|

Nothing else matters: Video games create sustained attentional selection away from task-irrelevant features

Abstract: Feature-based attention allocates resources to particular stimulus features and reduces processing and retention of unattended features. We performed four experiments using self-paced video games to investigate whether sustained attentional selection of features could be created without a distractor task requiring continuous processing. Experiments 1 and 2 compared two versions of the game Two Dots, each containing a sequence of images. For the more immersive game post-game recognition of images was very low, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…A final insight is on the effect of game genre on learning in games. We found that game task-based attention moderates learning in a fast-moving action game but Cutting, et al [28] also found the same attentional selection effect on learning with slow moving "self-paced" games with no requirement for fast reactions or decisions. They concluded that game tasks direct attention by the formation of an "attentional set" [59] of task relevant features which is formed by the initial instructions and feedback that players receive while learning the game.…”
Section: Theoretical Implications and Design Insightssupporting
confidence: 50%
See 2 more Smart Citations
“…A final insight is on the effect of game genre on learning in games. We found that game task-based attention moderates learning in a fast-moving action game but Cutting, et al [28] also found the same attentional selection effect on learning with slow moving "self-paced" games with no requirement for fast reactions or decisions. They concluded that game tasks direct attention by the formation of an "attentional set" [59] of task relevant features which is formed by the initial instructions and feedback that players receive while learning the game.…”
Section: Theoretical Implications and Design Insightssupporting
confidence: 50%
“…This was an online study that participants completed on their own computers via a browser. It was inspired by Cutting, et al [28]'s study in which participants played a game containing a set of changing images and attentional focus was then measured by testing their post-game recognition of the images.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Games are defined as voluntary and immersive activities that entertain users in a way that is separate from the real world (Barclay & Bowers, 2020;Cutting et al, 2020;Huang et al, 2019;Ijaz et al, 2020). All games have the following characteristics: fantasy, rules and objectives, sensory stimuli, challenge or level of difficulty, mystery in the game, interaction, and the amount of control one has over the game (Chen et al, 2021;Hügel & Davies, 2022;Maheu et al, 2018;Tsai & Tsai, 2020).…”
Section: History Teaching and Videogamesmentioning
confidence: 99%
“…One example of navigating this issue may be drawn from the practice of one member of the research team. To avoid the risk that either their game, or the playtime associated with their game, would not be representative of the real experiences of gamers, they 'cloned' (that is copied the gameplay) of popular casual mobile games Two Dots (Cutting et al, 2020) and Hey, that's my fish! .…”
Section: Custom Games With Built-in Data Hooksmentioning
confidence: 99%